Noradrenaline Modulates Visual Perception and Late Visually Evoked Activity - Gelbard-Sagiv, Hagar; Magidov, Efrat; Sharon, Haggai; Hendler, Talma; Nir, Yuval (Current biology, 2018)
An identical sensory stimulus may or may not be incorporated into perceptual experience, depending on the behavioral and cognitive state of the organism. What determines whether a sensory stimulus will be perceived? While different behavioral and cognitive states may share a similar profile of electrophysiology, metabolism, and early sensory responses, neuromodulation is often different and therefore may constitute a key mechanism enabling perceptual awareness. Specifically, noradrenaline improves sensory responses, correlates with orienting toward behaviorally relevant stimuli, and is markedly reduced during sleep, while experience is largely “disconnected” from external events. Despite correlative evidence hinting at a relationship between noradrenaline and perception, causal evidence remains absent. Here, we pharmacologically down- and upregulated noradrenaline signaling in healthy volunteers using clonidine and reboxetine in double-blind placebo-controlled experiments, testing the effects on perceptual abilities and visually evoked electroencephalography (EEG) and fMRI responses. We found that detection sensitivity, discrimination accuracy, and subjective visibility change in accordance with noradrenaline (NE) levels, whereas decision bias (criterion) is not affected. Similarly, noradrenaline increases the consistency of EEG visually evoked potentials, while lower noradrenaline levels delay response components around 200 ms. Furthermore, blood-oxygen-level-dependent (BOLD) fMRI activations in high-order visual cortex selectively vary along with noradrenaline signaling. Taken together, these results point to noradrenaline as a key factor causally linking visual awareness to external world events. [Display omitted] [Display omitted] •Noradrenergic drugs modulate sensitivity and accuracy of human visual perception•Noradrenaline increases the fidelity of late EEG visual responses•Noradrenaline selectively modulates BOLD fMRI responses in high-order visual cortex•NE is a key factor causally linking visual awareness to external world events Gelbard-Sagiv, Magidov et al. pharmacologically down- and upregulated NE signaling while subjects performed visual detection and discrimination tasks. They demonstrate that NE modulates perceptual sensitivity and accuracy, as well as late visually evoked EEG and fMRI responses, suggesting a key enabling role for NE in perceptual awareness.